(untitled) (American Journal of Social Development and Entrepreneurship, 2025)
Driven by the digital wave, the transformation of digital education is becoming the only way for the innovation and development of colleges and universities. Digital education in colleges and universities not only refers to the digitalization of educational tools, but also to the multi-level teaching system digitalization of education, teaching, management and resource utilization. Based on this, by analyzing the current situation of digital development and problems in domestic universities, summarizing relevant experience, we put forward the diversified summary of digital education and teaching forms to summarize the feedback of improving digital classroom teaching. This article referred to approximately 80 relevant literature. These documents cover multiple aspects such as digital education, educational management innovation, and digital teaching models in universities, ensuring the comprehensiveness and depth of the research. Priority should be given to research results published within the past 5 years to ensure the timeliness and relevance of research conclusions. Literature is directly related to digital education and innovative development in universities, with a focus on research on educational tools, teaching methods, management models, and resource utilization. Including research results from both domestic and international sources, in order to compare the development of digital education under different cultural backgrounds. case analysis and comparative demonstration to explore the path of innovative education management of higher education and put forward some suggestions.